P5 eHealth: An Agenda for the Health Technologies of the Future - Pravettoni, Gabriella; Triberti, Stefano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access volume focuses on the development of a P5 eHealth, or better, a methodological resource for developing the health technologies of the future, based on patients$1 (Bpersonal characteristics and needs as the fundamental guidelines for design. It provides practical guidelines and evidence based examples on how to design, implement, use and elevate new technologies for healthcare to support the management of incurable, chronic conditions. The volume further discusses the criticalities of eHealth, why it is difficult to employ eHealth from an organizational point of view or why patients do not always accept the technology, and how eHealth interventions can be improved in the future. By dealing with the state-of-the-art in eHealth technologies, this volume is of great interest to researchers in the field of physical and mental healthcare, psychologists, stakeholders and policymakers as well as technology developers working in the healthcare sector. .s
Introduction -- Chapter 1. A ''P5'' Approach to Healthcare and Health Technology; Gabriella Pravettoni and Stefano Triberti -- Chapter 2. The Development and Testing of the iManagement Cancer: The Experience of a Personalized eHealth Platform for Cancer Patients' Empowerment; Chiara Renzi and Stefan Kiefer -- Chapter 3. Primary, Secondary and Tertiary Prevention of Acute and Chronic Diseases through eHealth: A Practical Overview; Dario Monzani, Silvia Francesca Maria Pizzoli -- Chapter 4. An Introduction to Personalized eHealth; Lucrezia Savioni and Valeria Sebri -- Chapter 5. Predictive/ Precision Medicine; tbd -- Chapter 6. Participatory Aspects of ICT infrastructures for Cancer Management; Haridimos Kondylakis, Lefteris Koumakis, Manolis Tsiknakis and Kostas Marias -- Chapter 7. Psycho-Cognitive Factors Orienting eHealth Development and Evaluation; Alessandra Gorini and Gabriella Pravettoni -- Chapter 8. Role of Next Generation Sequencing Technologies in Personalized Medicine; Giuseppe Curigliano -- Chapter 9. User Centered Design Approaches and Methods for P5 eHealth; Stefano Triberti et al -- Chapter 10. Ethical Issues in P5 eHealth; Virginia Sanchini -- Conclusion.
Keywords: Clinical health psychology; Quality of life; Computers and civilization; Positive psychology; Health Psychology; Quality of Life Research; Computers and Society; Positive Psychology